Research methods for adult educators in Africa - Chilisa, Bagele; Preece, Julia; Unesco Institute for Education (Hamburg, Germany : UNESCO Institute for Education ; Cape Town, South Africa : Pearson Education, 2005)
This book explores and critiques existing research paradigms, presen ts African counter-arguments and examples, and proposes methodologies m ore appropriate for African contexts. The emphasis is on African realit ies, values and ways of knowing.--Publisher's description.
Contexts -- Foundations of inquiry -- African perspectives -- Doing a literature review -- Getting started -- Carrying out a survey -- Work ing with survey data -- Qualitative research -- Doing a qualitative stu dy -- Combining methods -- Action research -- Feminist research -- Rese arch ethics -- Writing up and disseminating research.
Includes bibliographical references and index.
Keywords: Adult education -- Research -- Africa; Adult education -- Africa -- Methodology; Adult education teachers -- Training of -- Africa